Sosialisasi Konsep Bankable dalam Pengelolaan Bank Sampah: Studi Pengabdian Masyarakat di Desa Mangunjaya, Kabupaten Bekasi - Suparyati, Agustina; Sumiyarti, Sumiyarti; Thomas, Rahmadianti (PT. Cendekia Sapta Indonesia, 2025)
This community service program aimed to enhance the financial management capacity of the ASRI Waste Bank in Mangunjaya Village, Tambun Selatan District, Bekasi Regency, by introducing the concept of bankable practices. The main problem faced by the waste bank administrators was the reliance on manual bookkeeping, which was prone to data loss and inefficiency. The program was implemented through training on preparing simple financial reports using Microsoft Excel, complemented by mentoring and the provision of one operational laptop. The activity was attended by 29 participants, consisting of administrators and community members. The evaluation results indicated improved understanding of digital financial recording, with 85% of participants able to prepare simple transaction reports independently after the training. This program contributes to strengthening the transparency, accountability, and sustainability of community-based waste bank management.